The Role of Diffusion-weighted MRI and Follow-up Contrast-enhanced MRI in Correlation with the Adnexa MR Scoring System in the Diagnosis of Uterine Appendage Tumors - B. P. Olimov; F. A. Kossov; O. N. Strel’tsova; V. O. Panov; I. V. Panichenko; Yu. V. Buydenok; I. E. Tyurin (Вестник рентгенологии и радиологии, 2019)
The paper analyzes the data available in the foreign and Russian literature over the past 10 years on main radiodiagnostic techniques and approaches in case of ovarian space-occupying lesions, by using both ultrasonic color Doppler mapping and complex MRI approaches in combination with routine MRI, diffusion-weighted MRI studies, and follow-up contrast-enhanced MRI. It shows that only the comprehensive introduction of the above radiodiagnostic techniques can achieve the necessary sensitivity and specificity of diagnosis of ovarian tumors. The system for assessing the risk index for ovarian tumor malignancy is discussed, by taking into account the menopausal status, the tumor marker CA-125, and ultrasonographic findings. The paper presents the Adnexa MR scoring system based on the breast imaging-reporting and data system (BI-RADS) that gives schemes for calculating and analyzing the risk of ovarian tumor malignancy in terms of certain MR criteria.